1991
DOI: 10.1177/001088049103100424
|View full text |Cite
|
Sign up to set email alerts
|

De Facto Security Standards: Operators at Risk

Abstract: Hotel security standards required by law tell only half the story: Actual court decisions are equally valid when it comes time to enforce the rule of "reasonable care ." Our survey of hotel owners and operators collected data about court-mandated security standards and we discuss which of those standards hoteliers consider important and which are controversial SUCCESSFUL MANAGEMENT involves being able to predict and control situations, people, or things. If something can be anticipated, managers must have in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Although the hospitality industry shares some similar features with other industries (e.g. the service industry), several studies have pointed out that the hospitality industry has some unique characteristics (Brotherton, 1999;Grönroos, 1984;Hansen et al, 2004;Hemmington, 2007;Jayawardena, 2000;King, 1995;O'Connor, 2005;Rutherford and McConnell, 1991). A distinctive characteristic of the hospitality industry is the affiliation with guests, whereas in the service industry, the relationship between the service providers and customers is economical (King, 1995).…”
Section: Characteristics Of the Hospitality Industry And Servant Leadershipmentioning
confidence: 99%
“…Although the hospitality industry shares some similar features with other industries (e.g. the service industry), several studies have pointed out that the hospitality industry has some unique characteristics (Brotherton, 1999;Grönroos, 1984;Hansen et al, 2004;Hemmington, 2007;Jayawardena, 2000;King, 1995;O'Connor, 2005;Rutherford and McConnell, 1991). A distinctive characteristic of the hospitality industry is the affiliation with guests, whereas in the service industry, the relationship between the service providers and customers is economical (King, 1995).…”
Section: Characteristics Of the Hospitality Industry And Servant Leadershipmentioning
confidence: 99%
“…Hotels can be the site of many types of crime such as theft, fraud, public order issues and prostitution (Gill et al, 2002) and terrorism (Paraskevas, 2013). Based on a survey of the top 50 American hotels, Rutherford and McConnell (1991) ranked the top 10 security concerns of hotel management from the greatest to the least as follows: training employees to report and deal with criminal activities, having adequate lighting, having lock systems, monitoring criminal behavior to secure the property, controlling access to guest areas, patrolling guestroom floors by well-trained security personnel, suggesting potentially dangerous areas around the hotel to guests, remotely monitoring by security guards, using armed safety personnel in high-crime-rate areas and providing training for armed safety personnel. Consequently, the crime rate has become one of the most critical factors in international hotels' selection of locations in host countries (Assaf et al, 2015).…”
Section: How Crime Affects Hoteliers Travel Agencies and Dmosmentioning
confidence: 99%
“…Increasingly courts are holding that those acts which harm someone on the premises can be foreseen. Rutherford and McConnell[14] observed that as a result of these legal changes in the USA, “the hotel industry is now operating at greater risk than in the past”.…”
Section: Crime Does Not Pay ‐ It Costsmentioning
confidence: 99%